The role of human adipose-derived mesenchymal stem cell-derived exosomes in burn injury: a narrative review - Tang, Haoran; Wang, Qi; Xue, Jun; Shen, Liang; Duan, Xiaguang; Zhou, Biao (Frontiers in Bioengineering and Biotechnology, 2026)
Burn injuries constitute a significant global health concern, presenting both health hazards and economic challenges. Recently, human adipose-derived mesenchymal stem cell exosomes (hADSCs-Exo) have emerged as a cell-free therapeutic strategy for promoting burn wound healing. These nano-sized particles function through various mechanisms, including promoting cellular migration, angiogenesis, inflammation reduction, immune response modulation, collagen remodeling, and scar prevention. They exert these effects by activating critical signaling pathways such as PI3K/Akt, IL-17RA/Smad, and mTOR. This review summarizes the biological characteristics and research relevance of hADSCs-Exo in burn injury management and discusses their translational implications.